A Lost Life: Three Studies in Socialism and Nationalism - Naylor, James (Labour / Le Travail, 1989)
The article reviews the book, "A Lost Life: Three Studies in Socialism and Nationalism," by David Howell.
Keywords: GENERATION of Boomers: The Pattern of Railroad Labor Conflict in 19th-Century America; A (Book); LABOR market; Nonfiction; REVIEWS; STROMQUIST; Shelton; books

Working-Class History in English Canada in the 1980s : An Assessment - Naylor, James (Acadiensis: Journal of the History of the Atlantic Region / Revue d'histoire de la region atlantique, 1989)
Slightly more than a decade ago "the new working-class history" emerged in Canada. It was an occasion marked by considerable enthusiasm as ringing manifestos promised "to bring back ordinary working people from their long exile on the margins of Canadian history". Existing institutional histories of trade unions and industrial relations, it was pointed out, told us remarkably little about the experience of workers or, in more general terms, about the nature of social class in Canadian history. On the basis of this critique of the existing historiography, a new generation of working-class historians set out an ambitious agenda. –From author's introduction